The nexus between higher education and economic growth: An empirical investigation for Pakistan - Amatul R. Chaudhary; Asim Iqbal; Syed Yasir Mahmood Gillani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
The study investigates the role of higher education in economic growth for Pakistan between 1972 and 2005 using the application of Johansen Cointegration and Toda & Yamamoto (1995) Causality approach in Vector Autoregressive (VAR) framework. It examines whether higher education affect long run economic growth in Pakistan. The empirical analysis reveals that there is a long run relationship between economic growth and higher education, which suggests that these variables are necessary for each other. The empirical results of causality test indicate that there exists a unidirectional causality running from economic growth to higher education and no other direction of causality found between these variables.
Keywords: 330; Pakistan; Higher Education; Economic Growth; Cointegration and Causality